Analysis of Complementary Yoga Therapy Against Drug Abuse in Adolescents - Indirawaty; Kurnia Rahma Syarif; Rosita Genggeng; Sumirah (Health Media, 2020)
Data Riskdesdes (2018) shows mental prevalence continues to increase. In addition, emotional prevalence in older people> 15 years rose from 6% to 9.8%. World Drug Report data reports that 5% of the world's population uses addictive substances. Addictive substance users Update 15 years to 64 years (Syahrial, 2015). The method that can be used to help control depression using narcotics is complementary yoga therapy (Streeter et al, 2012). The design of this study was quasi-experimental with one group pretest posttest design. The subjects of this study were 40 people according to the criteria. The results of the study are based on paired t test results obtained by the value of the statistical test results obtained p value (0,000) <0.05 which means given a score of knowledge scores between before and published the results of the statistical test evaluation obtained p value (0,000) <0.05 which means there are differences in scores before and after the intervention.